2015
DOI: 10.1016/j.jpubeco.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Do lottery payments induce savings behavior? Evidence from the lab

Abstract: This paper presents the results of a laboratory experiment designed to investigate whether the option of a Prize Linked Savings (PLS) product alters the likelihood that subjects choose to delay payment. By comparing PLS and standard savings products in a controlled way, we find strong evidence that a PLS payment option leads to greater rates of payment deferral than does a straightforward interest payment option of the same expected value. The appeal of the PLS option is strongest among men and selfreported lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Prospect theory probability weighting is also the motivation behind prize-linked savings products that are generally illegal in the United States but that have a long history and some popularity in other counties where they are allowed (Kearney et al 2010). Whether prizelinked savings products actually increase savings is an open empirical question, although one recent paper finds suggestive evidence from a laboratory experiment that lottery-like payouts lead to greater consumption deferrals than do standard linear interest rates (Filiz-Ozbay et al 2013). …”
Section: Behaviorally Informed Incentivesmentioning
confidence: 99%
“…Prospect theory probability weighting is also the motivation behind prize-linked savings products that are generally illegal in the United States but that have a long history and some popularity in other counties where they are allowed (Kearney et al 2010). Whether prizelinked savings products actually increase savings is an open empirical question, although one recent paper finds suggestive evidence from a laboratory experiment that lottery-like payouts lead to greater consumption deferrals than do standard linear interest rates (Filiz-Ozbay et al 2013). …”
Section: Behaviorally Informed Incentivesmentioning
confidence: 99%
“…In a laboratory experiment, Filiz-Ozbay et al (2015) find that a prize-based incentive makes subjects more willing to defer payment to a later date than an equivalent expected value fixed interest rate. Atalay et al (2014) conduct an online experiment and find that introducing a prize-linked savings product to a budget allocation task both increases savings and reduces lottery expenditures.…”
mentioning
confidence: 98%
“…Another approach has been prize-linked savings (PLS). The PLS approach uses accounts that reward account holders using a lottery-like drawing in which the chance of winning is proportional to the balance in the account (Filiz-Ozbay et al, 2015; Kearney et al, 2010). The goal of these accounts is to capitalize on the appeal of gambling to incentivize people to invest in their personal savings account.…”
Section: Prior Efforts Informed By Psychologymentioning
confidence: 99%
“…The goal of these accounts is to capitalize on the appeal of gambling to incentivize people to invest in their personal savings account. Research has shown that these tools are most appealing to men, lottery players, and individuals with relatively low account balances (Atalay et al, 2014; Filiz-Ozbay et al, 2015). Although most evidence supporting PLS stems from lab and online experiments, this work still suggests that these accounts may be a partial solution to encourage individual investment in personal savings.…”
Section: Prior Efforts Informed By Psychologymentioning
confidence: 99%